Homalometron moraveci n. sp. (Digenea: Apocreadiidae) in the yellowfin goatfish, Mulloidichthys vanicolensis (Valenciennes, 1831) (Perciformes: Mullidae), from New Caledonia and the Great Barrier Reef, with a checklist of digeneans of Mulloidichthys species - Bray, Rodney A.; Justine, Jean-Lou; Cribb, Thomas H. (Zootaxa, 2007)
Homalometron moraveci n. sp. is described from the yellowfin goatfish, Mulloidichthys vanicolensis, from the waters off New Caledonia and from the Swain Reefs of the Great Barrier Reef. Its unique combination of narrow, elongate body and long hermaphroditic duct reaching well into the hindbody, distinguish this species from all other species of Homalometron. A checklist of species of digeneans reported in species of Mulloidichthys shows that most of the records are of members of the Opecoelidae and this is the first record of an apocreadiid from this host genus.